PENINGKATAN BERPIKIR KREATIF SISWA MELALUI PENDEKATAN OPEN-ENDED DI SMP NEGERI 1 MILA - Muhammad Andri (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2017)
The use of methods that are not good in the teaching and learning process can weaken students' creative thinking abilities, reduce cognitive abilities, eliminate critical thinking, and do not establish optimal interaction between teachers and students. Deficiency results in decline and decline in education. The open-ended approach is a problem formulation that is used openly in problem solving, to find out how the teacher's efforts in teaching and student activities improve the creative thinking process. This study used qualitative research methods. Qualitative research seeks to describe, reveal, and explain symptoms or phenomena that occur in the field by describing and analyzing them. The technique of data collection was carried out by conducting library research, observation, interviews and documentation. The research was conducted at SMP Negeri 1 Mila, Pidie Regency. Data analysis is done by giving meaning to the data that has been generated and from that meaning a conclusion can be drawn. Checking the validity of the data is done by using data triangulation techniques, by comparing data from the results of literature studies, observations, interviews and documentation. The process of students' creative thinking activities in learning through an open-ended approach shows that students are increasingly focused, enthusiastic in participating in the learning process, students feel interested in learning openly, are happy and excited, participate and show responses in obtaining curiosity about the problems being studied. Students' creative thinking abilities on the tasamuh subject are students who have a smooth learning process and are able to present their ideas, have curiosity about the problems discussed, have the courage to express opinions with confidence, are able to explore and understand problems well and show sensitivity. In the process of increasing students' creative thinking through an open-ended approach, there are several problems and advantages of its own.